Quality Evaluation of EPC to BPMN Business Process Model Transformation - Khudori, Ahsanun Naseh; Kurniawan, Tri Astoto; Ramdani, Fatwa (Journal of Information Technology and Computer Science, 2020)
Due to the expressiveness of BPMN for representing the business processes, it has replaced EPC as a de-facto process modelling standard. As such, enterprises require to transform their existing EPC business process models to BPMN to keep their competitiveness. ARIS Architect & Designer, as a popular business process modelling tool, provides a model transformation feature, e.g., EPC to BPMN. For the sake of quality, it must guarantee that the resulting model has syntactic correctness and syntactic completeness. However, there is currently limited scientific approach available to evaluate the quality of the model transformation in ARIS Architect & Designer. This study proposes an evaluation of model transformation in ARIS Architect/Designer based on syntactic correctness and syntactic completeness criteria using an experimental approach. The result shows the model transformation in ARIS Architect/Designer has not completely fulfilled the criteria. The result opens further research challenges to improve the quality of EPC to BPMN model transformation.